Ras Signaling Inhibitors Attenuate Disease in Adjuvant-Induced Arthritis via Targeting Pathogenic Antigen-Specific Th17-Type Cells - Zayoud, Morad; Marcu-Malina, Victoria; Vax, Einav; Jacob-Hirsch, Jasmine; Elad-Sfadia, Galit; Barshack, Iris; Kloog, Yoel; Goldstein, Itamar (Frontiers in Immunology, 2017)
The Ras family of GTPases play an important role in signaling nodes downstream to T cell receptor and CD28 activation, potentially lowering the threshold for TCR activation by autoantigens. Somatic mutation in NRAS or KRAS may cause a rare autoimmune disorder coupled with abnormal expansion of lymphocytes. T cells from Rheumatoid Arthritis (RA) patients show excessive activation of Ras/MEK/ERK pathway. The small molecule farnesylthiosalicylic acid (FTS) interferes with the interaction between Ras GTPases and their prenyl-binding chaperones to inhibit proper plasma membrane localization. In the present study, we tested the therapeutic and immunomodulatory effects of FTS and its derivative 5-fluoro-FTS (F-FTS) in the rat adjuvant-induced arthritis model (AIA). We show that AIA severity was significantly reduced by oral FTS and F-FTS treatment compared to vehicle control treatment. FTS was as effective as the mainstay anti-rheumatic drug methotrexate, and combining the two drugs significantly increased efficacy compared to each drug alone. We also discovered that FTS therapy targeted the CFA-induced in vivo induction of Th17 and IL-17/IFN- producing "double positive" cells, together with reduced serum levels of the Th17-associated cytokines IL-17A and IL-22. By gene microarray analysis of effector Th-cells from CFA-immunized rats, we determined that FTS abrogated the mycobacterium tuberculosis heat-shock protein 65 (Bhsp65)-induced transcription of a large list of autoimmunity relevant genes (e.g. Il17a/f, Il22, Ifng, Csf2/GM-CSF, Lta, and Il1a). Moreover, this gene list (n=50) showed significant overlap with well-established annotated inflammatory/immune response gene sets. In Conclusions, FTS and F-FTS display immunomodulatory effects in AIA, linked to inhibition of the Th17-type response to a dominant arthritogenic antigen. Hence, targeting Ras signal-transduction cascade is a potential novel therapeutic approach for RA.